Improvement of diabetes indices of care by a short pharmaceutical care program - SANCAR, MESUT; RABUŞ, ŞULE (SPRINGER, 2009)
Objective Diabetes mellitus is a serious health problem associated with an increased mortality and morbidity. The association of improved glycemic control with sustained decrease in the rate of complications has been shown in randomized clinical trials. Pharmaceutical care is a relatively new concept in Turkey; yet, there are no recorded routine pharmaceutical care programs. Therefore, we aimed to assess the impact of a short pharmaceutical care program conducted in the community pharmacy setting, on the indices of diabetes care of type 2 diabetic patients, particularly those regarding glycemic control and high blood pressure management. Setting The study was carried out at eight community pharmacies in Pendik district of Istanbul. Method All patients who visited any of the eight pharmacies through the pre-determined 1-week period were questioned for the presence of type 2 diabetes. Patients who reported to be type 2 diabetic (n = 67) were informed about the study and invited to involve. During this prospective longitudinal study, pharmaceutical care was provided to the patients by the same clinical pharmacist. The 3 month pharmaceutical care period consisted of six pharmacy visits. Main outcome measure: The main outcome measures were the improvement in glycemic control and blood pressure control; while, weight control, self-monitoring of blood glucose, compliance and being under physician-control were also assessed. Results The study was conducted on 43 patients who accepted to involve. Fasting blood glucose was lowered by a mean of 23% over 3-months from an initial value of 167.2 mg/dl. Number of patients reaching the desired blood glucose goals increased from 16.3% to 39.5%. Systolic and diastolic blood pressures also significantly fell over 3 months (mean reductions were 10.9 mmHg for the systolic and 9.3 mmHg for the diastolic blood pressure). Number of patients reaching the desired blood pressure goal increased from 30.2% to 51.2%. Conclusion Our short-course pharmaceutical care program yielded measurable improvements in clinical indicators of diabetes and comorbidity management. The results suggest that the pharmacist is a beneficial key component of integrated care for patients with type 2 diabetes. We think that the positive results observed in this first reported pharmaceutical care program on diabetes in Turkey can be motivating and encouraging for all community pharmacists.
Keywords: Diabetes; Pharmaceutical care; Glycemic control; Blood pressure; Clinical pharmacist; Turkey; BLOOD-PRESSURE; COMMUNITY PHARMACY; OUTCOMES; MANAGEMENT; MODEL; COMPLICATIONS; HYPERTENSION; MELLITUS; IMPACT